Purification of West Pasaman Patchouli Oil by Complexometry Methods to Improve the Quality and Feasibility of the Business - Marlina, Lenny; Kasim, Anwar; Anggraini, Tuty (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This study aims to analyze the quality of purified patchouli oil, determine the most effective chelator in complexometric purification and assess the feasibility of the refining business. Patchouli oil purification was done using optimal chelating conditions identified in previous research. The chelators used were EDTA (2.5%), citric acid (2%), and tartaric acid (1.5%). The design used was a Completely Randomized Design (CRD) with one factor, namely three types of chelates with three replications. The results of testing physical and chemical properties were analyzed by ANOVA, followed by DNMRT at the 5% level. The best chelator was selected using the MADM-SAW method. Meanwhile, the business feasibility analysis used B/C ratio, R/C ratio, BEP, NPV, IRR, and ROI parameters. This research shows that citric acid is the best chelator for refining patchouli oil. The characteristics of the refined oil are reddish yellow, a specific gravity of 0.9597 g/ml, solubility in ethanol 1:10, an acid number of 2.32 mg KOH/g, an ester number of 7.45 mg KOH/g, Fe content of 0.94 mg/kg, and patchouli alcohol of 29.25%. The business feasibility analysis shows that the patchouli oil refining business is feasible with a Net B/C value of 3.7, R/C of 1.3, product BEP of 849 kg/year, and price BEP of Rp. 913.891,-/kg, NPV of IDR 1.078.107.098, IRR of 177%, and ROI of 30.86%. Contribution to Sustainable Development Goals (SDGs):SDG 1: No PovertySDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 15: Life on Land